2003
DOI: 10.1105/tpc.010538
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Vitamin C Contents Modulate Plant Defense Transcripts and Regulate Genes That Control Development through Hormone Signaling[W]

Abstract: Vitamin C deficiency in the Arabidopsis mutant vtc1 causes slow growth and late flowering. This is not attributable to changes in photosynthesis or increased oxidative stress. We have used the vtc1 mutant to provide a molecular signature for vitamin C deficiency in plants. Using statistical analysis, we show that 171 genes are expressed differentially in vtc1 compared with the wild type. Many defense genes are activated, particularly those that encode pathogenesis-related proteins. Furthermore, transcript chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
377
3
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(402 citation statements)
references
References 52 publications
19
377
3
3
Order By: Relevance
“…Based on the finding that application of the antioxidant ascorbate can restore susceptibility to B. cinerea [20], it is tempting to speculate that sitiens-induced resistance is caused by an interaction between the xanthophyll cycle and the ROS-buffering ascorbate-gluthatione cycle (Figure 3). In support of this, a mechanistic link between ABA biosynthesis and ascorbate has been demonstrated [21], which showed that low ascorbate in the Arabidopsis vtc1 (vitamin C1) mutant stimulates ABA production. The sitiens mutation in tomato blocks the last step in ABA biosynthesis.…”
Section: Erd15 (Early Responsive To Dehydration 15)mentioning
confidence: 85%
See 2 more Smart Citations
“…Based on the finding that application of the antioxidant ascorbate can restore susceptibility to B. cinerea [20], it is tempting to speculate that sitiens-induced resistance is caused by an interaction between the xanthophyll cycle and the ROS-buffering ascorbate-gluthatione cycle (Figure 3). In support of this, a mechanistic link between ABA biosynthesis and ascorbate has been demonstrated [21], which showed that low ascorbate in the Arabidopsis vtc1 (vitamin C1) mutant stimulates ABA production. The sitiens mutation in tomato blocks the last step in ABA biosynthesis.…”
Section: Erd15 (Early Responsive To Dehydration 15)mentioning
confidence: 85%
“…The conversion of violaxanthin into zeaxanthin is catalyzed by violaxanthin de-epoxidase (VDE) and requires oxidation of ascorbate into de-hydro ascorbate. As a result, reduced levels of ascorbate in the vtc1 (vitamin C1) mutant stimulate ABA biosynthesis [21]. By contrast, enhanced VDE activity antagonizes ABA production, reduces ascorbate levels and promotes conversion of reduced glutathione (GSH) into oxydized glutathione (GSSG).…”
Section: How Do Plants Resist Pathogens?mentioning
confidence: 99%
See 1 more Smart Citation
“…It also inhibited the oxidation of coniferyl alcohol by peroxidase leads to synthesis of lignin, another important defense-related compound (Ye et al, 1990). Pastori et al (2003) showed that many defense genes, particularly those that encode pathogenesis related-proteins were activated in Arabidopsis mutant deficient in biosynthesis of ascorbic acid. In the present study, a negative correlation was observed between ascorbic acid content and PM severity (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The vtc1 mutant, isolated by its sensitivity to ozone, has lower activity of the AsA biosynthetic enzyme GDPMan pyrophosphorylase, resulting in a 70% lower AsA content compared to the wild type (Conklin et al, 1999). Two recent studies on this mutant have demonstrated that both leaf photosynthesis and the capacity of the antioxidant system are largely un-changed (Veljovic-Jovanovic et al, 2001), while some plant defense-related transcripts are up-regulated (Pastori et al, 2003). The effect of low AsA on xanthophyll cycle activity was studied recently in the AsAdeficient mutant vitamin c-2 (vtc2; Mü ller-Moulé et al, 2002).…”
mentioning
confidence: 99%